Electromagnetic Shielding Hybrid Nanogenerator for Health Monitoring and Protection. (13th November 2017) - Zhang, Qian; Liang, Qijie; Zhang, Zheng; Kang, Zhuo; Liao, Qingliang; Ding, Yi; Ma, Mingyuan; Gao, Fangfang; Zhao, Xuan; Zhang, Yue
Abstract: Nowadays, mankind faces increasingly energy crisis and electromagnetic radiation pollution. An energy harvester with function of protecting human health from electromagnetic radiation is a desirable solution to this problem. Here, a stretchable electromagnetic shielding hybrid nanogenerator (ES‐HNG) is reported which can not only scavenge thermal and mechanical energy from living environment but also protect and monitor human health. The ES‐HNG is capable of transforming mechanical and thermal energy to electricity based on triboelectric, piezoelectric, and pyroelectric effects. To be devised as a computer keyboard cover, ES‐HNG takes about 200 s to charge a capacitor to 3 V by typing. The stored energy can drive the portable devices successfully. Besides, the ES‐HNG eliminates electromagnetic radiation of computer completely due to its unique electromagnetic shielding property. A large range of electromagnetic wave (frequency is between 0 and 1.5 GHz) is shielded more than 99.9978% by the ES‐HNG. Moreover, the ES‐HNG is able to monitor human health by attaching it on human abdomen to be a self‐powered sensor. This work opens up a new prospect of harvesting energy effectively as well as protecting/monitoring human health from electromagnetic radiation surroundings. Abstract : An electromagnetic shielding hybrid nanogenerator (ES‐HNG) is fabricated by integrating triboelectric nanogenerator and pyroelectric‐piezoelectric nanogenerators. The ES‐HNG is capable of harvesting thermal and mechanical energies from ambient environment, monitoring, and protecting human health from electromagnetic radiation.